Recovery potential of biopolymer (B-P) formulation from Solanum tuberosum (waste) starch for enhancing recovery from oil reservoirs - Oluwasanmi Olabode; Temiloluwa Ojo; Tomiwa Oguntade; Doyin Oduwole (Energy Reports, 2020)
Enhanced Oil Recovery (EOR)is a researching area targeted at mobilizing reservoir trapped oil. Several applications of EOR technology provides an added possibility to squeeze out more oil from the reservoir, perhaps about 20%. However, need for innovation in production at a cost effective method and environmentally friendly is required. Polymer flooding is one of the best EOR methods, and is primarily employed to increase oil recovery by sweep improvement. The aim of this research work is primarily the designing of a specific biopolymer product with emphasis on polymer in-situ rheology and polymer flow performance examined in Enhanced oil recovery. This research involves the injection of potato peel (Solanum tuberosum) derived bio-polymer solution at different concentrations by performing simultaneous experiments at ambient conditions using a reservoir permeability testing equipment (RPT). In this novel polymer formulation, Solanum tuberosum (waste) Starch (most abundant, naturally occurring biodegradable polymers) was hydrolyzed chemically. Experimental results show that viscosity of B-P solution increases at every increment of polymer quantity reducing the mobility ratio. Several runs of flooding experiments were achieved the Reservoir permeability tester (RPT). The incremental oil recoveries vary 52%, 60%, to 74% of original oil in place (OOIP) subject to the polymer concentration.
Keywords: 330; Oil recovery; Biopolymer; Polymer flooding